Analysis Of The Regional Revenue And Expenditure Budget (APBD) For The Financial Performance Assessment Of The Asahan Regency Regional Government For 2019-2024 - Susi Susi; Anggi Pratama Nasution; Hendra Saputra (Jurnal Akuntansi, Manajemen dan Bisnis Digital, 2026)
The research study aims to analyze the financial performance of the Asahan Regency Government for the 2019-2024 period by applying a quantitative descriptive methodology, utilizing secondary data from the Regional Budget Realization Report. The analysis was conducted using five main financial ratios, namely the Financial Independence Ratio, the Regional Original Revenue (PAD) Effectiveness Ratio, the Regional Financial Efficiency Ratio, the Operational and Capital Expenditure Harmony Ratio, and the Revenue Growth Ratio. The research results show that the financial performance of the Asahan Regency Government still faces challenges in the aspect of Financial Independence, which is classified as very low (an average of 11.55%) with an Instructive pattern, indicating a high dependence on central transfer funds. The PAD Effectiveness Ratio is generally in the fairly effective category, with an average of 97.54%. The Regional Financial Efficiency Ratio is classified as inefficient, with an average of 100.17%, where ideally the efficiency percentage is below 100%. The Expenditure Harmony Ratio shows a relatively harmonious proportion, with an average of 65.54% of Operational Expenditure and 14.07% of Capital Expenditure. Meanwhile, the Revenue Growth Ratio shows unstable conditions, with contractions in 2020 and 2023, and the highest positive growth of 11.11% in 2024. Overall, the Asahan Regency Government needs to increase fiscal independence by optimizing PAD, maintaining consistent revenue effectiveness, and managing expenditures to be more efficient and sustainable.